Vendor Performance Evaluation Using Kraljic’s Purchasing Portfolio Matrix and Analytic Hierarchy Process Method (Case study: PT Pertamina Trans Kontinental Central Jakarta) - Akbar, Muhammad Syauqil; Pramono, Susatyo Nugorho Widyo (Proceeding International Conference on Religion, Science and Education, 2024)
Vendor performance evaluation is one of the factors supporting the company’s business because having a good quality vendor can indirectly improve the company’s performance and have an impact on the company’s profitability. The research was conducted based on criteria using the Vendor Performance Indicator (VPI), namely Quality, Cost, Delivery, Flexibility, Responsiveness, at PT Pertamina Trans Kontinental, Central Jakarta. The use of the Analityc Hierarchy Process (AHP) method is carried out to measure the performance of several vendors and the results obtained for vendor L get the highest weight compared to other vendors, namely 2.076, vendor A (2.045), vendor B (2.017), and vendoir K (1.985). Classification of items is also carried out using the Kraljic’s Matrix method and is divided into four quadrants, namely the Leverage quadrant containing Rope, Turalic, Gasket and Ship Paint, with the recommendation of a call of contract strategy. The Non-critical quadrant contains Camera, Antenna, Radio, Dapra Chain, Battery, Aluminium Anode, and Dry Battery, with recommendations for regular trading and purchasing card strategies. The Strategic quadrant contains Filter, Main Engine, Cable Shore Connection, and Liferaft, with recommendations for partnership contract and accept a locked-in strategy. While the Bottleneck quadrant contains Impeller, Pasut, Power Supply, Dapra Tyre, and HRU EPIRB with the recommendation of a call of contract strategy. Based on these results, the company can see the assessment of several vendors and implement strategies that have been suggested by classification using the Kraljic’s matrix analysis method.